Usability Testing pada Aplikasi Kas Berbasis Android dan Teknologi API menggunakan Metode System Usability Scale - Al Muharom, Nurul Ibnu; Suarna, Nana; Dana, Raditya Danar (Jurnal Informatika Terpadu, 2024)
Cash management applications are used to store transaction data and create cash in and cash out reports that are more effective than using books. However, currently no usability testing has been carried out so it is quite difficult to determine future application development steps. The aim of this research is to measure the level of usefulness of an Android-based cash management application using the System Usability Scale (SUS) method, namely a 10-question Likert scale questionnaire distributed to respondents with the final result being a score of 0-100. The number of respondents was 15 people who were CV employees. Jaya Mukti. This test was carried out to determine the level of user convenience and satisfaction. The results of the research obtained a score of 84.7, this score shows a percentile level of 96%, Grade Scale A, Acceptability Ranges are in the Acceptable category, meaning acceptable, and the Adejctive Rating is in the Excellent category. If correlated with NPS, it falls into the promoter category, meaning users will recommend the application. These results show that the application can be accepted by users and is very good and above the established usability value standards. This research also produced 4 recommendations for improvement based on the results of questionnaire answers so that they can be used as evaluation for future application development.